Management strategies and outcome of blunt traumatic abdominal wall defects: a single centre experience. Issue 9 (September 2019) - Karhof, S; Hietbrink, F; Boot, R; van Wessem, K.J.P; Leenen, L.P.H; Simmermacher, R.K.J
Highlights: There is a low incidence of traumatic abdominal wall injuries following blunt abdominal trauma of less than 1%. It is seen mostly in polytrauma patients with several concomitant injuries. When using a mesh in the treatment of TAWD, significantly less recurrences are seen when compared to primary closure. Either when used in the acute as in the delayed setting. Following traumatic abdominal wall defects patients suffer lower (overall) quality of life, mainly due to limitations in daily activities, mobility and pain. This corresponds to previous studies investigating quality of life in severely injured trauma patients. Abstract: Introduction: Traumatic abdominal wall defects (TAWDs) following blunt trauma are uncommon injuries with an incidence reported less than 1%. Improved diagnostics and subsequent early detection of otherwise rare injuries raise more questions concerning their treatment. There is lack of consensus on treatment and timing of TAWD. The aim of this study was to analyse the management strategy and outcomes of these injuries in our level I trauma centre. Methods: All trauma patients who presented with a TAWD at our trauma centre between 2007 and 2016 were retrospectively reviewed. Blunt abdominal wall injuries were classified, patient characteristics, concomitant injuries and treatment characteristics were recorded. In addition, telephone surveys were conducted to assess patient reported quality of life. Results: In a period of nearly ten years 21 patients with a TAWD were treated in our hospital, approximately 0.17% of all admitted trauma patients. Seventeen patients were classified as polytrauma patient. Seventeen patients underwent surgical repair in whom 5 recurrences occurred. All of the recurrences were in patients treated without mesh repair (p = 0.03). The quality of life in terms of EQ-VAS was similar for patients treated with and without mesh repair and reasonable when compared to the reference population. Overall quality of life was lower compared to the reference population, mainly due to limitations in daily activities, mobility and pain. Conclusion: Using mesh in the treatment of TAWD, in our hands, showed significantly less recurrences compared to primary closure. We therefore recommend the use of mesh in the repair of TAWDs, both in the acute as well as in the delayed setting when feasible.